The New Farm Owners: Corporate Investors Lead the Rush for Control of Overseas Farmlands - (GRAIN), Genetic Resources Action International (Kasarinlan: Philippine Journal of Third World Studies; Vol 26 No 1-2 (2011): Food Sovereignty in Southeast Asia)
Land grabbing has been going on for centuries. One only has to think of Columbus “discovering” America and the brutal expulsion of indigenous communities that this unleashed, or white colonialists taking over territories occupied by the Maori in New Zealand and by the Zulu in South Africa. It is a violent process very much alive today, from China to Peru. Hardly a day goes by without reports in the press about struggles over land, as mining companies such as Barrick Gold invade the highlands of South America or food corporations such as Dole or San Miguel swindle farmers out of their land entitlements in the Philippines. In many countries, private investors are buying up huge areas to be run as natural parks or conservation areas. And wherever you look, the new biofuel industry, promoted as an answer to climate change, seems to rely on throwing people off their land. Something more peculiar is going on now, though. The two big global crises that erupted in 2008—the world food crisis and the broader financial crisis that the food crisis has been part of (GRAIN 2008a)—are together spawning a new and disturbing trend toward buying up land for outsourced foodproduction.
Keywords: land grabbing, farmland, biofuels, world food crisis